Cyst Fluid Biomarkers - Diagnosis and Prediction of Malignancy for Cystic Lesions of the Pancreas - Raman, Aadhithya (Visc Med, 2018)
Pancreatic cysts are common, and are identified in 2–13% of individuals undergoing cross-sectional imaging. Intraductal papillary mucinous neoplasms (IPMNs) and mucinous cystic neoplasms (MCNs) are pancreatic cysts which are precursors to pancreatic adenocarcinoma. Currently available tools are imperfect at differentiating IPMNs and MCNs from other, benign types of pancreatic cysts. The role of molecular markers in the evaluation of pancreatic cysts and the identification of cysts with high-grade dysplasia or invasive adenocarcinoma is reviewed.